Some Aspects of State-Building Processes in Carpathian Ukraine on the Eve of the Second World War - Vehesh, М.; Vidnyanskyj, S. (Міжнародні зв’язки України: наукові пошуки і знахідки, 2020)
Autonomous Subcarpathian Rus’, and subsequently independent Carpathian Ukraine, existed for an extremely short period of time: from October 1938 to the second half of March, 1939. Despite this fact, there was such a rapid development of political events in the country that the attention of the whole world was drawn to Carpathian Ukraine. This also applies to the researchers who, at the end of the 1930s, began to study the history of Carpathian Ukraine. The declaration of independence on March 14, 1939 was explained by the desire of the Ukrainian population of the region for freedom. However, the disintegration of Czechoslovakia and the declaration of independence by Slovakia were also of great importance for this act. Despite some spontaneity and haste, this historical event in the life of not only Transcarpathian Ukrainians, but of the entire Ukrainian people was of great historical importance. After January 21, 1919, it was the second attempt to declare to the whole world that Ukrainian nation is alive and ready for state life. Although this act of declaration of independence, ratified on March 15, 1939 at the Soim of Carpathian Ukraine, was more symbolic than real politics, it played a large role in forming the self-consciousness of the entire Ukrainian nation. It was during the period of Carpathian Ukraine that a kind of transition from consciousness of Transcarpathian Ruthenians to Transcarpathian Ukrainians ended. In the late 1930s, Carpathian Ukraine was the only state where a small branch of the Ukrainian people proclaimed their independence and declared their desire to live a state life. The Ukrainians who were part of the USSR, as well as the Ukrainians under the control of Poland and Romania didn’t have such opportunity. However, they treated Carpathian Ukraine as an area where an attempt was made to restore Ukrainian statehood. On this basis, it is necessary to consider the formation of the Carpatho-Ukrainian state as the second stage — after the liberation contest of 1918–20’s — in the struggle for the creation of Ukrainian state formation on a separate Ukrainian territory.